Relatedness within and between leks of golden-collared manakin differ between sexes and age classes. (18th August 2018) - Fusani, Leonida; Barske, Julia; Natali, Chiara; Chelazzi, Guido; Ciofi, Claudio
Abstract : Male manakins might help their relatives to attract mates if they cannot get any themselves. Male manakins gather in "leks" to display; however, only a few males obtain copulations. Larger leks attract more females, but why unsuccessful males should join the lek has puzzled researchers for years. We found that relatedness among displaying males is higher than among immature males and females, suggesting that displaying with related successful males might attract indirect fitness benefits. Abstract: Several hypotheses have been advanced to explain the evolution of leks, a mating system in which males aggregate at display sites where females choose their mates. Only a small proportion of males obtain copulations, and why other males join the lek remains unexplained. One hypothesis has called kin selection into play: if juvenile males join leks where their relatives display and contribute to attract females to the lek, they can gain indirect fitness benefits. We investigated the genetic structure of 8 leks of golden-collared manakin, a tropical Passerine. Adult court-holder males, females, and immature males were caught within lek boundaries and the geographical location of the courts was recorded. For court-holding males, within-lek relatedness among 4 leks was significantly higher than average across-lek relatedness. Courts of more closely related males were not spatially associated within leks. Relatedness among immature males was relatively lower, yet higher within than between leks. Values of relatedness and genetic differentiation among leks were even lower for females. Thus, leks were composed of males that were more related to each other than to other males of the population, and the degree of relatedness decreased from court-holding males to immature males to females. This suggests that immature males explore several leks and eventually join those where their relatives display, whereas females appear to visit leks randomly with respect to relatedness. Our results provide support for the hypothesis that kin selection influences the evolution of lekking behavior in this species.